Exploring Teachers’ Awareness and Attitudes Towards Ergonomics Practices in the Classroom - Ezeoguine, Ebere Pearl; Kasumu, Rebecca Yinka (The Indonesian Institute of Science and Technology Research, 2025)
This study adopted correlational research designed to explore teachers’ awareness and attitudes toward ergonomics practices in the classroom. The study was carried out at community secondary schools in Nigeria. The Population of the study is 152 teachers from the two schools. A sample of 76 teachers was used for the study. The simple random sampling technique was used for the study. The instrument used for the study is a structured questionnaire titled Exploring Teachers’ Awareness and Attitudes towards Ergonomics Practices in the Classroom (ETAAEPC) with 20 items. Face and content validity were used for the study. A reliability coefficient of 0.74 was obtained. Mean and Z-test were the statistical tools used for the study to compare two schools to observe differences in the teachers’ awareness and attitude. The study found that with the increasing use of technology in classrooms, ergonomic principles related to the use of computers, tablets, and other devices are becoming more relevant, and also teachers who are knowledgeable about digital ergonomics can better support students in using technology safely. Based on the findings, the researchers recommended that teacher training institutions and professional development bodies should develop and deliver targeted professional development workshops and training sessions.